On the origin of worries about modern health hazards: experimental evidence for a conjoint influence of media reports and personality traits - Witthöft, Michael; Bailer, Josef (Psychology & health, 2017)
Objective: Worries about health threatening effects of potential health hazards of modern life (e.g. electric devices and pollution) represent a growing phenomenon in Western countries. Yet, little is known about the causes of this growing special case of affective risk perceptions termed Modern Health Worries (MHW). The purpose of this study is to examine a possible role of biased media reports in the formation of MHW.Design: In two experiments, we investigated whether typical television reports affect MHW. In Study 1, 130 participants were randomly assigned to a film on idiopathic environmental intolerance (IEI) or a control film about cystic fibrosis. In Study 2, 82 participants were randomly assigned to either a film on the dangers of electromagnetic fields or a control condition.Main outcome measures: Increases in MHW after sensational media reports.Results: In Study 1, only participants high on the personality trait of absorption revealed increased MHW after watching the IEI film. In Study 2, specifically worries about radiation were found to be elevated after watching the film on the dangers of electromagnetic fields compared to the control film.Conclusion: The results of both studies reveal a significant and specific influence of sensational short mass media reports on MHW. The influence of potential moderators such as absorption remains to be clarified.
Gesehen am 28.08.2018